Progression of aerobic and anaerobic thresholds in cardiac rehabilitation: heart failure vs coronary artery disease. (3rd October 2022) - Custodio, P M; Santos, A R; Moreno, L; Mendes, M
Abstract: Background: Cardiac rehabilitation (CR) aims at the maintenance and potential recovery of cardiovascular function through an exercise program. Programs may be started with cardiopulmonary exercise test (CPET) in order to assess aerobic and anaerobic thresholds (VT1 and VT2), and to optimize the exercise prescription. In our center, most CR programs are in-hospital for the first 3–6 months, after which patients undertake another CPET to evaluate the progression and follow up with a home-based training schedule. Aim: To compare the progression in aerobic and anaerobic thresholds after CR program in patients with heart failure (HF) or post-acute event in coronary artery disease (CAD). Stratify the results based on ejection fraction to see which patients show the most benefit. Methods: A retrospective single center study using data from patients that were included in a CR program between January 2016 and December 2020. Patients without measurable ventilatory thresholds 1 and 2 (VT 1 and VT2) at both CPET were excluded as were those that didn't complete the CR program. VT 1 and VT2 progression was compared among patients referred to the CR program due to HF and CAD. A sub-analysis was performed based on having reduced ejection fraction (rEF) (<50% on echocardiogram). Results and discussion: A total of 136 patients were included (57, 51±13, 47 YO; 80, 9% (n=110) male; 44, 2% (n=60) had reduced ejection fraction. 46 patients were referred to CR due to HF and 90 due to CAD. Most patients referred to CR due to CAD underwent complete revascularization (82, 2%) beforehand. The average time between the acute coronary event and the beginning of the CR program was 208 days. Even though the stunned myocardial phase would be expected to be resolved by the time the CR program was started, patients with CAD showed the steepest progression in VT1 and VT2 thresholds. Patients with CAD with preserved ejection fraction are the subgroup with the most robust progression in VT1 and VT2 when compared with rEF. This difference was statistically significant when the two etiologies were compared (p value = 0, 047 for VT1 and 0, 031 for VT2) – Table 1. Conclusion: Patients with CAD and preserved ejection fraction exhibit the faster progression in aerobic and anaerobic thresholds in CR when compared to HF patients. Funding Acknowledgement: Type of funding sources: None.